Parents' experiences of managing their child's postoperative pain at home: an exploratory qualitative study. Issue 17 (27th June 2016) - Longard, Julie; Twycross, Alison; Williams, Anna M.; Hong, Paul; Chorney, Jill
Abstract : Aims and objectives: To understand parents' experiences of managing their child's postoperative pain at home. Background: Recent changes in children's health care services often shift the responsibility of managing children's postoperative pain to parents. Although pain management is important for good postoperative outcomes, it can be a challenging task for families, and children's pain is often under‐managed. Design: This qualitative study used semi‐structured interviews to explore parents' experiences of managing their child's postoperative pain at home. Methods: Participants were parents of 10 typically developing 5‐ and 6‐year olds, who underwent (adeno)tonsillectomy, and experienced no complications leading to hospitalisation in the postoperative period. One‐on‐one interviews were conducted with parents within three months of their child's surgery. Interviews were transcribed verbatim and content analysis was used to identify themes in parents' experiences. Results: All children experienced some postoperative pain. Parents' experiences of managing their child's pain were impacted by balancing the pros and cons of administering analgesic medications, managing the emotional and psychological effects of their child's pain, as well as parents' information needs. Conclusions: Most parents' information needs were met yet they still struggled to manage their child's pain. These findings provide insight into some of the barriers that make this process challenging for many families, and what health care centres can do to help support parents manage their child's postoperative pain at home. Relevance to clinical practice: The results of this study may aid in the design of interventions that will support parents when managing their child's postoperative pain at home and thus improve children's experiences.